Proceedings of the fifth biennial cross-campus conference on education: Controversies in education - Byron, Maria K. (School of Education, The University of the West Indies, 2001)
This volume contains papers delivered at the conference, which sought to provide a forum for open discourse on a wide range of controversial issues such as governance, curriculum, financing, assessment, gender, discipline, and teacher education. The organization seeks to bring together, as far as possible, papers with a related focus. Abstracts are provided for papers that were presented at the conference but not submitted for publication.
Biennial Cross-Campus Conference on Education, 5th, St. Augustine, Trinidad, April 7-9, 1999
Keywords: Educational environment